Reduction of Tet2 exacerbates early stage Alzheimer's pathology and cognitive impairments in 2×Tg-AD mice. (15th January 2020) - Li, Liping; Qiu, Yisha; Miao, Miao; Liu, Zhitao; Li, Wanyi; Zhu, Yiyi; Wang, Qinwen
Abstract: Abnormal modification of 5-hydroxymethylcytosine (5hmC) is closely related to the occurrence of Alzheimer's disease (AD). However, the role of 5hmC and its writers, ten-eleven translocation (Tet) proteins, in regulating the pathogenesis of AD remains largely unknown. We detected a significant decrease in 5hmC and Tet2 levels in the hippocampus of aged APPswe/PSEN1 double-transgenic (2×Tg-AD) mice that coincides with abundant amyloid-β (Aβ) plaque accumulation. On this basis, we examined the reduction of Tet2 expression in the hippocampus at early disease stages, which caused a decline of 5hmC levels and led young 2×Tg-AD mice to present with advanced stages of AD-related pathological hallmarks, including Aβ accumulation, GFAP-positive astrogliosis and Iba1-positive microglia overgrowth as well as the overproduction of pro-inflammatory factors. Additionally, the loss of Tet2 in the 2×Tg-AD mice at 5 months of age accelerated hippocampal-dependent learning and memory impairments compared to age-matched control 2×Tg-AD mice. In contrast, restoring Tet2 expression in adult neural stem cells isolated from aged 2×Tg-AD mice hippocampi increased 5hmC levels and increased their regenerative capacity, suggesting that Tet2 might be an exciting target for rejuvenating the brain during aging and AD. Further, hippocampal RNA sequencing data revealed that the expression of altered genes identified in both Tet2 knockdown and control 2×Tg-AD mice was significantly associated with inflammation response. Finally, we demonstrated that Tet2-mediated 5hmC epigenetic modifications regulate AD pathology by interacting with HDAC1. These results suggest a combined approach for the regulation and treatment of AD-related memory impairment and cognitive symptoms by increasing Tet2 via HDAC1 suppression.